Holocene rockfalls in the southern Negev Desert, Israel and their relation to Dead Sea fault earthquakes. Issue 2 (March 2014) - Rinat, Yair; Matmon, Ari; Arnold, Maurice; Aumaître, Georges; Bourlès, Didier; Keddadouche, Karim; Porat, Naomi; Morin, Efrat; Finkel, Robert C.
Abstract: Rockfall ages in tectonically active regions provide information regarding frequency and magnitude of earthquakes. In the hyper-arid environment of the Dead Sea fault (DSF), southern Israel, rockfalls are most probably triggered by earthquakes. We dated rockfalls along the western margin of the DSF using terrestrial cosmogenic nuclides (TCN). At each rockfall site, samples were collected from simultaneously exposed conjugate boulders and cliff surfaces. Such conjugate samples initially had identical pre-fall ("inherited") TCN concentrations. After boulder detachment, these surfaces were dosed by different production rates due to differences in post-fall shielding and geometry. However, in our study area, pre-rockfall inheritance and post-rockfall production rates of TCN cannot be evaluated. Therefore, we developed a numerical approach and demonstrated a way to overcome the above-mentioned problems. This approach can be applied in other settings where rockfalls cannot be dated by simple exposure dating. Results suggest rockfall ages between 3.6 ± 0.8 and 4.7 ± 0.7 ka. OSL ages of sediment accumulated behind the boulders range between 0.6 ± 0.1 and 3.4 ± 1.4 ka and support the TCN results. Our ages agree with dated earthquakes determined in paleoseismic studies along the entire length of the DSF and support the observation of intensive earthquake activity around 4–5 ka.